Steatocystoma multiplex suppurativa: a case report - Rainamira, Arlene; Krisnanti, Inge Ade; Rihatmadja, Rahadi; Suprapto, Novita; Surya, Danny (Explorer Front, 2023)
Introduction: Steatocystoma multiplex (SM) suppurativa is an inflammatory variant of SM, a benign hamartomatous disorder of pilosebaceous unit that usually occurs in early adulthood. Treatment responses are often disappointing due to widespread lesions and late diagnosis. This case report aimed to describe a male diagnosed with SM suppurativa to increase the knowledge and management of SM suppurativa. Case: A 23-year-old male came with multiple lumps on his neck, chest, back, and extremities over the last four years. On dermatological examination, yellow to skin-colored papules, nodules, and cysts, 0.3 to 2 cm in diameter, were observed with erythematous-to-hyperpigmented macules and scars over the lesions. Histopathological examination of the lesion showed cysts with pilosebaceous-like lining and sebaceous glands adhered to the cyst’s wall. The patient diagnosed with steatocystoma multiplex SM suppurativa was treated only with a topical antibiotic and corticosteroid. Discussions: Although the histopathological findings showed pathognomonic findings for SM, SM suppurativa was established as the working diagnosis based on the clinical and dermoscopic findings of inflammatory lesions. The biopsy of noninflammatory lesions might cause no sign of inflammation in the histopathological findings. Conclusions: Dermoscopic findings showed a yellow structureless area with diffuse erythematous borders and histopathological findings of a pilosebaceous-like layer with sebaceous glands adhering to the cyst wall and chronic inflammation is the hallmark of SM suppurativa.